Hubungan Pengetahuan dan Sikap Ibu terhadap Tumbuh Kembang Anak dalam Pencegahan Stunting - Harahap, Vivi Chairani; Putri, Eka Syah; Rahma, Desfi; Agustina, Dewi (MODELING: Jurnal Program Studi PGMI, 2023)
Toddlers are a golden period where there are important times in the process of human growth and development. Stunting is a chronic nutritional problem in toddlers which is characterized by shorter height compared to children their age. Posyandu (integrated service post) is the government's effort to facilitate the Indonesian people in obtaining maternal and child health services. The main purpose of the posyandu is to prevent an increase in maternal and infant mortality during pregnancy, childbirth, or afterward through empowerment in which one of the Percut Village programs, Percut Sei Tuan District in dealing with maternal and child problems is the posyandu which is carried out 6 times per month and 1 time implementation. posbindu. Objective: This study aims to describe the level of knowledge of mothers about stunting in Percut Village, Percut Sei Tuan Dusun 17 Percut Village. Methodology: This research is quantitative with descriptive method. Respondents in this study were mothers who had toddlers at the Posyandu in Dusun 17 with data collection techniques through interviews, as well as distributing questionnaires. Result : The majority of maternal age is in the early adult category as many as 19 respondents with a percentage (63.3%). It can be seen that the mother's last education was dominant at the high school education level, where the respondents were 22 (73.3%). Meanwhile, it can be seen that the majority of mothers work as housewives (IRT) as many as 28 respondents (93.3%). It is also seen that the monthly income earned by the majority of Percut Village residents is above Rp. 1,500,000 as many as 17 respondents (56.7%).